ESTUDOS ESTRUTURAIS POR CRISTALOGRAFIA E MODELAGEM COMPUTACIONAL DA LIPASE DE PINHÃO MANSO (Jatropha curcas) E DA TRIOSE FOSFATO ISOMERASE DE Naegleria gruberi - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Knowledge of protein structures is of huge importance, since this information allows to understand the mechanisms through which proteins carry out their biological functions. Lipases constitute an enzymatic family capable to perform synthesis or hydrolysis of ester bonds of triacyl glycerols (TAGs) with long chain fatty acids.These enzymes are the theme of many investigations given their potential to be used in a wide variety of apllications involving chemicals with the ester functional group,e.g., in organic synthesis. On the other hand, structural knowledge of some enzymes is important for the development of new therapeutic drugs or even to contribute for the understanding of structural evolutionary features, like those belonging to metabolic pathways. In this work were accomplished the homology modeling of the lipase from Jatropha curcas and the structure determination of the triosephosphate isomerase from Naegleria gruberi from three X ray diffraction data sets. Among three experimental structures obtained, two belong to C2 space group, with different unit cells, and one to P4122 space group. Initial phases were obtained by molecular replacement procedure using the Phaser program and all structures were refined interactively with Coot and Phenix programs. In one structure it was possible to model three molecules of the precipitant agent Jeffamine present in the crystallization solution and one molecule of Tris buffer (placed at the active site). Structural comparisons were performed among the refined and validated model and some of its homologues, taking into account the differences observed in the structural-based alignment among them and characteristics noticed during the refinement procedure. Circular dichroism experiments have shown that thermal denaturation is irreversible to triosephosphate isomerase of Naegleria gruberi.
Keywords: Jatropha curcas; Naegleria gruberi; cristalografia; lipase; triose fosfato isomerase; estrutura tridimensional; Jatropha curcas; Naegleria gruberi; crystallography; lipase; Triosephosphate isomerase; three dimensional structure; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA